KONTRIBUSI PEMBELAJARAN PPKN TERHADAP PENEGAKAN KEDISIPLINAN SISWA DI SMPN 9 PALU DAN SMP AL-AZHAR PALU - Murfin, Andri (Katalogis, 2017)
This research was aimed to describe the discipline of the students of SMPN 9 Palu and SMP Al-AzharPalu, the role of Pancasila and Civic Education teachers in building the students’ discipline, and the students’ response toward the roles of the teachers in building discipline. The subjects of this research were students, Pancasila and Civic Education teachers and principal. In order to obtain deeper information, the sampling technique employed in this research was purposive sampling technique, which was done by determining the informants deliberately based on certain criteria or considerations. The data collection techniques used by the researcher were: observation, interview and questionnaire. The questionnaire data were analyzed using frequency table and percentage. Meanwhile, the interview and observation data were analyzed using qualitative approach through three stages, namely: Data Reduction, Data Presentation and Data Verification. The results of this research show that the discipline of the students of SMPN 9 Palu was categorized into good and the discipline of the students of SMP Al-AzharPalu was categorized into very good. The Pancasila and Civic Education teachers played their roles in building discipline through Pancasila and Civic Education learning strategies, Pancasila and Civic Education learning materials, Pancasila and Civic Education teachers’ example and school rules. The response of the students of SMPN 9 Palu toward the discipline building was categorized into strong, while the response of the students of SMP Al-AzharPalu was categorized into very strong. It can be concluded that students’ discipline should receive attention, either by school or parents, and thus requires cooperation between both parties. In addition, it is expected that teachers have not only the ability of transferring materials but also the creativity in managing learning process in the classroom and strict attitude as well as appropriate attitude as example.